Comparative evaluation of platelet indices in Preeclamptic and Non-Preeclamptic patients in the Enugu Metropolis - Edwin Obiorah Ohotu; Micheal Nneoma Queendalyn; Alphonsus Ogbonna Ogbuabor (Open Journal of Tropical Medicine - Peertechz Publications, 2023)
Preeclampsia (PE) is one of the most common causes of maternal mortality and morbidity. It complicates 5% - 6% of all pregnancies globally and up to 15% of pregnancies in Sub-Saharan Africa. The present study was designed to determine the values of platelet indices in preeclamptic patients compared to non-preeclamptic controls. A total of 70 patients comprising 35 preeclamptic cases and 35 non-preeclamptic controls aged 18-40 years were recruited for the study. Blood samples (3mls) were collected from patients for the estimation of platelet indices using the Mindray 530 BC automated hematology analyzer, Mindray, Japan. The data were analyzed by SPSS version 22 using T - test and Pearson correlation. The level of significance was set at p < 0.05 and the result was presented as mean + SD. The result revealed a significant increase in the MPV (13.5 + 0.18 vs. 09.4 + 0.20), PDW (16.2 + 0.037 vs. 06.0 + 0.19) and PLCR (38.0 + 1.19 vs. 26.2 + 1.19) between the preeclamptic patients and non-preeclamptic controls. There was a significant decrease in the PLT (174.1 + 15.5 vs. 231.1 + 15.05), PCT (1.9 + 0.14 vs. 3.3 + 0.75), and PLCC (60.7 + 3.24 vs. 69.4 + 3.17) for the preeclamptic cases compared to non-preeclamptic control. These findings may be useful in the management of the adverse outcomes of preeclampsia for the Enugu population.